2023
DOI: 10.3390/jof9030373
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Profiles Provide Insights into the Red-Stipe Symptom of Morel Fruiting Bodies

Abstract: The cultivation of true morels (Morchella spp., Morchellaceae, Ascomycota) has rapidly expanded in recent years, especially in China. Red stipe is a symptom wherein the stipe of morel fruiting bodies becomes red–gray, resulting in the gradual death of the affected fruiting bodies. The impact of red-stipe symptom occurrence on the development and nutritional quality of morel fruiting bodies remains unclear. Herein, morel ascocarps with the red-stipe symptom (R) and normal (N), artificially cultivated in the Fuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, the exact effects and molecular mechanisms underlying Morchella mycelial responses to adverse temperature stress during the vegetative growth period have not been fully elucidated, which may limit the further industrial cultivation of Morchella species [ 24 ]. It has been reported that insufficient nutrition at low or high temperatures may cause severe disease with red-stipe symptoms, resulting in growth cessation and rot of the fruiting body [ 25 ]. Therefore, elucidating the mechanism underlying the effect of temperature on mycelia is an important prerequisite for achieving stable and high yields of Morchella and has important guiding significance and application value for optimizing cultivation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact effects and molecular mechanisms underlying Morchella mycelial responses to adverse temperature stress during the vegetative growth period have not been fully elucidated, which may limit the further industrial cultivation of Morchella species [ 24 ]. It has been reported that insufficient nutrition at low or high temperatures may cause severe disease with red-stipe symptoms, resulting in growth cessation and rot of the fruiting body [ 25 ]. Therefore, elucidating the mechanism underlying the effect of temperature on mycelia is an important prerequisite for achieving stable and high yields of Morchella and has important guiding significance and application value for optimizing cultivation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional components in a microbial culture environment directly affect the efficiency and type of cell metabolic product synthesis [18,19]. In this study, the Box-Behnken response surface method was used to optimize the medium formulation of polysaccharides from MS-1 via liquid-submerged fermentation, and the polysaccharide MSL from MS-1 was isolated and extracted from the fermentation broth.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation methods are mainly based on the domestication of easy-to-fruit varieties, the utilization of exogenous nutrient bags, and suitable environmental conditions [11,13]. Despite remarkable breakthroughs in artificial cultivation, approximately half of morel cultivations experience low fruiting rates and difficulties in obtaining stable profits [9,12], caused by serious problems such as strain aging or degradation [9,14], fungal and bacterial diseases [12,[15][16][17], environmental fluctuations, and refined field management [11,13]. These problems place greater demands on understanding the developmental mechanism and biology of morels.…”
Section: Introductionmentioning
confidence: 99%